HUBUNGAN PENGETAHUAN IBU TENTANG GIZI DENGAN STATUS GIZI BALITA DI WILAYAH KERJA PUSKESMAS XIII KOTO KAMPAR TAHUN 2013 - Bintang Tantejo; Erwin Chriastianto; Tuti Restuastuti (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Nutritional status is the status or state of the body as food consumption andutilization of nutrients can be divided into the nutritional status of very thin, thin,normal and obese. Factors affecting the nutritional status of children is parentaleducation, parental knowledge and family economic factors. This research aims todetermine the relationship between mothers knowledge of nutrition with nutritionalstatus of children in the region of 13 health centers Koto Kampar in 2013. Thisanalytical research using cross sectional design with a number of respondents by 95people. Nutritional status was assessed using anthropometric measurements. Mothersassessment of the level of knowledge using a questionnaire. The result of the researchshowed nutritional status of 11.6% is very thin, 36.8% is thin, 28.4% normal dentalstatus and 23.2% is fat. The result of the research showed that knowledge level46.3% of mothers had less knowledge, 37.9% of mothers had enough knowledge and15.8% of mothers had good knowledge. Analysis of these result using the test resultobtained merging cells and there is a relationship between the level of knowledge ofmothers with nutritional status of children in the region of XIII health centers KotoKampar in 2013 with p < 0,05 in this researchKeyword : knowledge, anthropometric, nutritional status of children